Posted by **Tony** on Tuesday, March 20, 2007 at 9:03pm.

5x-2y=-5

y-5x=3

substitution

Substitute 5x +3 for y in the first equation, then solve it for x.

Substitute 5x +3 for y in the first equation, then solve it for x.

When I subsitute 5x+3 into the equation I get x=1/5 and y=2 is this correct?

You are close! Try x = -1/5 (y is correct).

Substitute the values into the original equations to check. If both equations check out with the values you found as solutions, then you know you are on the right track! :)

## Answer this Question

## Related Questions

- Algebra 1 - What is an equation of a line perpendicular to the line with ...
- ALGEBRA 1!PLZ HELP! - Use the Substitution method to solve the system of ...
- How do I do this.?(Math.) - Use the Substitution method to solve the system of ...
- substitution method - -x-4y=-14 2x=y+1 Let's look at your two equations. -x - 4y...
- substitution method - -3x+y=-5 x+2y=0 Your equations: -3x + y = -5 x + 2y = 0 ...
- Algebra - Please help to find x, y 1. 8x-y=17 6x+y=11 2. 5x-2y=17 2x+3y=3 ...
- Algebra 1 - 1.To solve the linear system below, which substitution of unkowns is...
- math - Solve systems by substitution 5x - 2y = -5 y - 5x = 3 Substitute 5x + 3 ...
- Alg-Substitution (check plz) - k well i had to use substitution to find the ...
- math - Not sure about this... Need to solve by substitution 8x - 4y = 16 y = 2x...